1998
DOI: 10.1104/pp.116.2.725
|View full text |Cite
|
Sign up to set email alerts
|

Formate Dehydrogenase, an Enzyme of Anaerobic Metabolism, Is Induced by Iron Deficiency in Barley Roots1

Abstract: To identify the proteins induced by Fe deficiency, we have compared the proteins of Fe-sufficient and Fe-deficient barley (Hordeum vulgare L.) roots by two-dimensional polyacrylamide gel electrophoresis. Peptide sequence analysis of induced proteins revealed that formate dehydrogenase (FDH), adenine phosphoribosyltransferase, and the Ids3 gene product (for Fe deficiency-specific) increased in Fe-deficient roots. FDH enzyme activity was detected in Fe-deficient roots but not in Fe-sufficient roots. A cDNA encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 46 publications
3
47
0
1
Order By: Relevance
“…3 and 4). In barley roots, the expression of FDH is induced by iron deficiency, an induction that appears to be a secondary effect of the oxygen deficiency resulting from iron deficiency (Suzuki et al, 1998). It has also been proposed that glycolysis may play an important role in the FDH expression in response to abiotic stresses (Hourton-Cabassa et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…3 and 4). In barley roots, the expression of FDH is induced by iron deficiency, an induction that appears to be a secondary effect of the oxygen deficiency resulting from iron deficiency (Suzuki et al, 1998). It has also been proposed that glycolysis may play an important role in the FDH expression in response to abiotic stresses (Hourton-Cabassa et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Fe-containing lipoxygenase (Hildebrand, 1989) and the storage protein ferritin (Gaymard et al, 1996) were also decreased in Fedeficient plants. In contrast, H ϩ -ATPase (Dell 'Orto et al, 2000), formate dehydrogenase (Suzuki et al, 1998), lysyl-tRNA synthetase (Giritch et al, 1997), and adenine phosphoribosyltransferase (Itai et al, 2000) were shown to be increased in expression or enzyme activity under Fe deficiency.…”
Section: Specific Changes In If In Cdna Clones For Reference Genesmentioning
confidence: 99%
“…These enzymes have been reported with differing cofactor requirements, electron acceptors, substrates and cellular locations (Hourton Cabassa et al, 1998). The FDHs NAD-dependent which have been extensively studied in both bacteria, yeast and plants, have been widely utilized in industry for NADH regeneration (Alekseeva, Savin & Tishkov, 2011;Hoelsch et al, 2013;Suzuki et al, 1998) …”
Section: Introductionmentioning
confidence: 99%